PERBEDAAN COGNITIVE PERFORMANCE ANTARA ANAK YANG TERINFEKSI CACING USUS DENGAN TIDAK TERINFEKSI CACING USUS - Kiking Ritarwan*, Hasan Sjahrir* (Neurona Majalah Kedokteran Neuro Sains, 2010)
INTRODUCTION SOIL TRANSMITTED HELMINTHIASES IS ONE OF THE PROBLEM IN PEOPLES HEALTHY ESPECIALLY IN DEVELOPING COUNTRIES IN INDONESIAN THE PREVALENCE IS HIGH 6080 IN THE SCHOOL AGE CHILDREN IN MILD INFECTION IT WAS FOUND GROWTH ABNORMALITY THAT IT CAUSED REDUCED COGNITIVE FUNCTION AND MALNUTRITION FOR CHILDREN IN ENDEMIC AREA MORE OVER WORM INFECTION RELATED TO CHANGING EDUCATION HELMINTHIASES HAS CLOSED RELATIONSHIP WITH HUMAN QUALITY BECAUSE IT CAN INFLUENCE HEALTHY NUTRITIONAL STATUS INTELEGENTIA PRODUCTIVITY AND LOW ECONOMIC STATUS